2006
DOI: 10.1016/j.ydbio.2006.02.044
|View full text |Cite
|
Sign up to set email alerts
|

D-six4 plays a key role in patterning cell identities deriving from the Drosophila mesoderm

Abstract: Patterning of the Drosophila embryonic mesoderm requires the regulation of cell type-specific factors in response to dorsoventral and anteroposterior axis information. For the dorsoventral axis, the homeodomain gene, tinman, is a key patterning mediator for dorsal mesodermal fates like the heart. However, equivalent mediators for more ventral fates are unknown. We show that D-six4, which encodes a Six family transcription factor, is required for the appropriate development of most cell types deriving from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 48 publications
6
46
0
Order By: Relevance
“…This is comparable with the migration speeds of other Drosophila cells that move in collectives, e.g. ovarian border cells [21-60 mm/h (Bianco et al, 2007;Prasad and Montell, 2007;Tekotte et al, 2007)] and male-specific SGPs [(12.3 mm/h) (Clark et al, 2006)]. The mean migration rates of DECs were significantly lower in pyr 18 homozygous mutants (21.4±4.1 mm/h; n=9; two embryos),…”
Section: Research Articlesupporting
confidence: 77%
“…This is comparable with the migration speeds of other Drosophila cells that move in collectives, e.g. ovarian border cells [21-60 mm/h (Bianco et al, 2007;Prasad and Montell, 2007;Tekotte et al, 2007)] and male-specific SGPs [(12.3 mm/h) (Clark et al, 2006)]. The mean migration rates of DECs were significantly lower in pyr 18 homozygous mutants (21.4±4.1 mm/h; n=9; two embryos),…”
Section: Research Articlesupporting
confidence: 77%
“…This finding is consistent with recently published data implicating D-six4 in embryonic mesodermal patterning in Drosophila. 17 Overexpression of bmp4 resulted in ventralization, which confirms a role of bmp4 in ventral mesendoderm formation (Table 2; Figure 4). 13,14 To assay the function of mutated Six2.1 and Bmp4, the human mutations were introduced into cDNA constructs of bmp4 and six2.1 by site-directed mutagenesis.…”
Section: Human Six2 and Bmp4 Mutations Disrupt Protein Functionsupporting
confidence: 66%
“…3d). The D-six4 gene also shows expression specific to this domain (18,19). Our labeling studies showed that this domain is subdivided into several small compartments of 2-12 cells with discrete gene expression profiles (see Fig.…”
Section: Resultsmentioning
confidence: 73%